2017
DOI: 10.1038/nm.4330
|View full text |Cite
|
Sign up to set email alerts
|

Silent hippocampal seizures and spikes identified by foramen ovale electrodes in Alzheimer's disease

Abstract: We directly assessed mesial temporal activity in two Alzheimer’s disease (AD) patients without a history or EEG evidence of seizures, using intracranial foramen ovale electrodes. We detected clinically silent hippocampal seizures and epileptiform spikes during sleep, a period when both were most likely to interfere with memory consolidation. These index cases support a model in which early development of occult hippocampal hyperexcitability may contribute to the pathogenesis of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
286
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(299 citation statements)
references
References 27 publications
10
286
1
2
Order By: Relevance
“…Altered PV IN inhibition on pyramidal cells is closely linked to abnormal network oscillations and cognitive functions. Network hyperexcitability and epileptiform events have been observed in most mouse models of AD (Palop et al, 2007, 2011; Busche et al, 2008; Palop and Mucke, 2009; Harris et al, 2010; Roberson et al, 2011; Yan et al, 2012; Busche and Konnerth, 2016) and in AD patients using high resolution recordings (Lam et al, 2017). Hypersynchronous network activities have been shown to emerge during reduced gamma oscillation, which is a rhythm that depends on the activities of fast-spiking PV INs and contributes to cognitive functions (Cardin et al, 2009; Sohal et al, 2009; Buzsáki and Wang, 2012; Sohal, 2012; Cho et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Altered PV IN inhibition on pyramidal cells is closely linked to abnormal network oscillations and cognitive functions. Network hyperexcitability and epileptiform events have been observed in most mouse models of AD (Palop et al, 2007, 2011; Busche et al, 2008; Palop and Mucke, 2009; Harris et al, 2010; Roberson et al, 2011; Yan et al, 2012; Busche and Konnerth, 2016) and in AD patients using high resolution recordings (Lam et al, 2017). Hypersynchronous network activities have been shown to emerge during reduced gamma oscillation, which is a rhythm that depends on the activities of fast-spiking PV INs and contributes to cognitive functions (Cardin et al, 2009; Sohal et al, 2009; Buzsáki and Wang, 2012; Sohal, 2012; Cho et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it remains difficult to study potential epileptiform activities in patients with conventional EEG electrodes because the abberant activity takes place in deep temporal structures. A recent study using foramen ovale electrodes positioned adjacent to the mesial temporal lobe revealed clinically silent hippocampal seizures and epileptiform spikes during sleep, a period especially important for memory consolidation (Lam et al, 2017). In urethane-anesthetized App NL-F mice, abnormal gamma oscillations were observed in the entorhinal cortex, including reduced theta-γ coupling and impaired phase-locking of layer 2/3 pyramidal cell spiking activities (Nakazono et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to increased incidence of seizures in AD patients (Vossel et al, 2017), a recent study revealed subclinical hippocampal seizures and spikes during sleep in AD patients (Lam et al, 2017). Studies of AD mouse models with cerebral Aβ and/or tau pathologies have demonstrated increased incidence of spontaneous or induced seizures, EEG evidence of global seizure-like activity, and increased excitability of hippocampal and entorhinal cortex projection neurons measured using intracellular electrodes (García-Cabrero et al, 2013; Kam et al, 2016; Kazim et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, age explains over 15% individual-level variation in module 4 (cortex), module 7 (hippocampus), and module 8 (all brain tissues). Notably, the hippocampus is associated with memory, in particular long-term memory, and is vulnerable to Alzheimer's disease (Lam et al 2017). In the module 4, GPR26 is found to be the top age-related gene.…”
Section: Fine Structures In Subtensors Of Similar Tissuesmentioning
confidence: 99%